2003
DOI: 10.1002/jcp.10267
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of the mesangial cell myofibroblast phenotype by actin polymerization

Abstract: Mesangial cells in diverse glomerular diseases become myofibroblast-like, characterized by activation of smooth muscle alpha-actin (alpha-SMA) expression. In cultured mesangial cells, serum-deprivation markedly increases alpha-SMA expression, cell size, and stress fiber formation. Since stress fibers are assembled from actin monomers, we investigated the hypothesis that alterations in stress fiber formation regulate alpha-SMA expression and hypertrophy. Human mesangial cells were treated with agents that disru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 86 publications
3
17
0
Order By: Relevance
“…There is evidence that treatment of HeLa cells with adenovirus infection or trypsin/EDTA, which lead to modifications in cell shape (rounding up) and motility, are not coupled to an alteration in the actin content (Blikstad and Carlsson, 1982). Cytoskeleton is a target for marine toxins known actin-depolymerizing toxin) causes a marked loss of Factin, but has no effect on cell morphology (Patel et al, 2003). In agreement with this, we found that the morphology of intestinal cells did not seem to be affected by any of the toxins that induced a notable effect on actin levels.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that treatment of HeLa cells with adenovirus infection or trypsin/EDTA, which lead to modifications in cell shape (rounding up) and motility, are not coupled to an alteration in the actin content (Blikstad and Carlsson, 1982). Cytoskeleton is a target for marine toxins known actin-depolymerizing toxin) causes a marked loss of Factin, but has no effect on cell morphology (Patel et al, 2003). In agreement with this, we found that the morphology of intestinal cells did not seem to be affected by any of the toxins that induced a notable effect on actin levels.…”
Section: Discussionmentioning
confidence: 99%
“…Mack et al (42) reported that smooth muscle differentiation marker gene expression is regulated by Rhokinase-mediated actin polymerization and that Rho-kinase inhibition blocks the synthesis of the ␣-SMA isoform. It also was shown that Rho-kinase regulates ␣-SMA promoter activity in glomerular mesangial cells (43) and induces mesenchymal transdifferentiation of proximal tubular cells (44). Further in vitro studies demonstrated that TGF-␤ 1 induces mesenchymal transdifferentiation through RhoA-dependent pathway (45).…”
Section: Figure 2 Photomicrographs Of Glomeruli (A Through E) Glomementioning
confidence: 95%
“…Enhanced expression of ␣-SMA is a marker of interstitial phenotypic changes in renal fibrosis, and these activated interstitial cells are known as myofibroblasts (36,38). It is interesting that it also has been revealed that the Rho-kinase signaling pathway plays a key role in the regulation of myofibroblastic transformation (22,(42)(43)(44)(45). In mouse kidneys with unilateral ureteral obstruction, treatment with a Rho-kinase inhibitor attenuated renal interstitial ␣-SMA expression and fibrosis (22).…”
Section: Figure 2 Photomicrographs Of Glomeruli (A Through E) Glomementioning
confidence: 99%
“…Furthermore, similar to renal tubular epithelial cells, mesangial cells also employ transdifferentiation into myofibroblasts in various glomerular diseases (19). This transdifferentiation is characterized by the activation of smooth muscle α-actin expression, and Rho-kinase inhibitors, Y-27632 and HA-1077, block this process in cultured renal mesangial cells (20). Finally, in mesangial cells, mechanical stress, which is considered to cause glomerular hypertension and glomerulosclerosis, enhances mitogen-activated protein kinase (MAP kinase) activity, stress fiber formation, and cellular proliferation (21).…”
Section: Role Of Rho / Rho-kinase In the Kidneymentioning
confidence: 99%